Cost-effectiveness of oral versus injectable disease modifying therapies in relapsing multiple sclerosis: a systematic review analysis - Mehdi Rezaee; Ramin Ravangard; Seyyed Morteza Mojtabaeian; Abdosaleh Jafari (BMC Health Services Research)
Abstract Background Multiple sclerosis (MS) is a chronic and progressive neurological autoimmune disease that affects the central nervous system. There are two types of drugs used to treat this disease: injectable and oral drugs. The present study aimed at systematically reviewing the cost effectiveness of oral versus injectable drugs. Methods The researchers searched the PubMed, Scopus, and Web of Science databases to find relevant studies. After removing the duplicates, two authors independently assessed the records. The studies that had conducted full economic evaluations of oral versus injectable drugs in MS patients were included. The Quality of Health Economic Studies (QHES) tool was also used to assess the quality of the studies. Results Thirty studies that had conducted the economic analysis of oral versus injectable therapies in MS patients were included in this review. The QHES scores for all records were generally high (≥ 77) and they were of good quality. The lowest and highest levels of incremental net monetary benefit were respectively obtained through the comparison of Fingolimod and Alemtuzumab (-1,419,333) and the comparison of Teriflunomide and Interferon β-1a (1,792,810). The amount of INMB (incremental net monetary benefit) in the comparisons between oral and injectable drugs showed that the highest and lowest amount of INMB calculated between) Fingolimod and injectable drugs, respectively, compared to (interferon β-1a) 98,253 and (Ocrelizumab) -212,417, the highest amount in dimethyl fumarate is also against (peginterferon β-1a) 191,470 and the lowest against (alemtuzumab) -124,333, Teriflunomide against injectable drugs is the highest against (peginterferon β-1a) 89,956 and the lowest (Ocrelizumab) − 194,169, as well as Cladribine compared to injectable drugs, the highest was compared to (interferon β-1a) 236,430 and the lowest (Ocrelizumab) was 23,965. Conclusion A large number of health economic evaluations of disease-modifying therapies (DMTs) in MS were available at the international level, the comparison of which was difficult and sometimes contradictory. However, despite the difference in the results, Cladribine tablets were cost-effective in all studies compared with injectable drugs. In addition, the present study could be of great importance for policymakers and other beneficiaries regarding the cost-effectiveness of the aforementioned drugs.